Clinical Profile and Outcome in Children with Post Diphtheritic Paralysis in a Tertiary Care Hospital in South India - Gowda, Vykuntaraju K; Vignesh, Sukanya; Benakappa, Asha K; Benakappa, Naveen; Shivappa, Sanjay K (Iranian Journal of Child Neurology, 2022)
Abstract Objectives Post-Diphtheritic Paralysis (PDP), one of the most severe complications of Diphtheria, is caused by exotoxin of Corynebacterium diphtheria. Since there has been a resurgence of diphtheria in India in the recent years attributed to a number of epidemiological factors, this study was planned. Materials & Methods Thirty-five children with Post-Diphtheritic paralysis (PDP) were studied in a tertiary care hospital in Southern India. Neurological complications occurred in 38.5% of 91 patients of faucial diphtheria. Thirteen (37.1%) children were unimmunized, 12 (34.3%) were partially immunized, two (5.7%) were completely immunized and unknown status in eight (22.6%). Isolated bulbar palsy in 20 (57.1%) and bulbar palsy followed by limb weakness was seen in 15(42.9%) of patients. The first symptoms of PDP occurred 5-34 days after the onset of local diphtheria infection. Eleven (31.4%) out of 35 patients had received anti-toxin between days 5-7 of illness. Ventilation dependent respiratory failure occurred in three (8.6%) patients with PDP. Nine patients (25.7%) had evidence of co-existent myocarditis while myocarditis with renal failure was seen in two (5.7%) patients. Four (11.4%) patients died, three from severe cardiomyopathy and one from aspiration. Demyelinating neuropathy was noted in 64%. Bulbar palsy recovered by 4-7weeks, while limb symptoms improved by 6-17weeks. Conclusion Post-Diphtheritic paralysis should be considered in any child presenting with bulbar palsy/ quadriparesis following previous history of fever/ sore throat. Awareness and availability with timely administration of ADS within 48 hours is important to reduce PDP, as antitoxin seems ineffective if administered after the second day of diphtheritic symptoms.